"I've always known this place, familiar as a room in our house" : engaging with memory, loss and nostalgia through sculpture - Reed, Kesayne (Rhodes University, Faculty of Humanities, Department of Fine Art, 2015)
My exhibition draws on Andreas Huyssen's notion of memory sculpture to articulate my own sense of loss and trauma, due to the divorce of my parents. Within my work I explore the effects that divorce had on me and how it has disturbed my normative understanding of home and family. I have created scenarios alluding to the family home that I have manipulated in order to convey a sense of nostalgia and loss. By growing salt crystals over found objects and/or cladding them in salt, I attempt to suggest the dual motifs of preservation (a nostalgic clinging to the past) and destruction (due to the salt's corrosive properties). In this way, the salt-crusted objects serve as a metaphor for a memory that has become stagnant, and is both destructive and regressive. The objects encapsulate the mind's coping methods to loss. In my mini thesis, I discuss characteristics of memory sculpture as a response to trauma, drawing on Sigmund Freud's differentiation between mourning and melancholia. I also unpack how objects and traces (such as photographs) may act as nostalgic triggers, inducing a state of melancholic attachment to an idealised past. I address these concerns in relation to selected works by Doris Salcedo and Bridget Baker, and also situate them in relation to my own art practice.
Keywords: Memory in art; Loss (Psychology) in art; Nostalgia in art; Sculpture -- Themes, motives; Art therapy; Sculpture -- Exhibitions